Primer of Geriatric Urology - Guzzo, Thomas J.; Drach, George W.; Wein, Alan J. (Springer New York : Imprint: Springer, 2013)
Primer of Geriatric Urology provides a review of the demographics of our aging urologic population and their unique needs. Chapters review alterations that must be considered in the initial evaluation of the aging patient, and follow with practical suggestions for development of the management plan, whether by counseling, medication, invasive procedure or foregoing procedures. Complications, especially likely in the elderly, are also discussed. The volume also provides a review of the use of necessary adjunctive services such as home care or hospice in the context of Medicare in the USA. An important chapter provides hints on urology practice in a nursing home. The volume concludes with analysis of specific geriatric entities seen in urology practice. Primer of Geriatric Urology will be of great value to urologists, residents, fellows and allied health professionals including physician's assistants and nurse practitioners who treat urologic patients. Additionally, this book will also be of interest to primary care providers who treat elderly patients with urologic problems.